2022
DOI: 10.1021/acs.accounts.2c00041
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Histones in DNA Damage and Repair within Nucleosome Core Particles: Mechanism and Applications

Abstract: Conspectus DNA is damaged by various endogenous and exogenous sources, leading to a diverse group of reactive intermediates that yield a complex mixture of products. The initially formed products are often metastable and can react to yield lesions that are more biologically deleterious. Mechanistic studies are frequently carried out on free DNA as the substrate. The observations do not necessarily reflect the reaction environment inside human cells where genomic DNA is condensed as chromatin in the nucleus. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…2016 ). These histones can catalyze DNA cleavage in nonphysiological, low-pH environments when protonated ( Ren et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…2016 ). These histones can catalyze DNA cleavage in nonphysiological, low-pH environments when protonated ( Ren et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…3A, S8, and S9, Table S1 ‡). 28,39,43 PBDA-modied NCPs were irradiated for various durations, and the DNA-histone crosslink yields were quantied by SDS-PAGE (Fig. S10 ‡).…”
Section: Mechanistic Study Of Photo-reactions Of Pbda Analogue 7 With...mentioning
confidence: 99%
“…19,[21][22][23] We have previously demonstrated that a C4 ′oxidized abasic site (C4-AP) reacts with primary amines to form stable conjugates. [24][25][26][27][28] In the present study, we designed and synthesized an analogue of C4-AP, photo-caged 2-butene-1,4dial (PBDA, Fig. 1B), as a new photo-crosslinker for identifying DNA-binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…DNA–protein cross-links (DPCs) block transcription and replication and as such pose a significant biological threat. , The first known DNA-dependent proteases that are postulated to be constituents of a general DPC repair pathway have been discovered in the past decade. DPC repair deficiency has already been associated with the Ruijs–Aalfs syndrome, which gives rise to premature aging and early onset liver cancer. ,, DPCs are produced by a variety of chemical agents, including aldehydes and chemotherapeutic agents. Transient DPCs formed between histone proteins and the epigenetic base 5-formylcytosine (5fC) play a role in regulating transcription in cells. DPCs also result from nucleobase oxidation, including ionization induced by a variety of UV-absorbing photochemical reagents and the direct effect of ionizing radiation, which is used to treat more than 50% of cancer patients. Ionizing radiation produces DPCs in greater quantities than either DNA–DNA interstrand cross-links or double-strand breaks. , Despite the prevalence and biological significance of radiation-induced DPC formation within chromatin, there is a gap in our knowledge regarding their formation from nucleobase radical cations that are generated via direct ionization. We report our investigation of this chemistry in nucleosome core particles (NCPs), the monomeric component of chromatin.…”
Section: Introductionmentioning
confidence: 99%